The Effectiveness of AI-Based Application Duolingo in Enhancing Students’ Vocabulary Mastery among Indonesian EFL Learners - Yuniar Yuniar; Syawal Syawal; Hijrah Hijrah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to determine the effectiveness of the use of the artificial intelligence-based application (AI-Based Application) Duolingo in improving vocabulary mastery of EFL (English as a Foreign Language) students in Indonesia. This study used a descriptive quantitative approach with a single-group pre-test and post-test design involving 20 students of class VII C of SMP Negeri 1 Mappakasunggu. Data were collected through vocabulary tests, questionnaires, and classroom observations. The results showed a significant increase in students' vocabulary mastery, marked by an increase in the average score from 61 (fair category) in the pre-test to 78 (good category) in the post-test. Most students gave a positive perception of the use of Duolingo, especially regarding the gamification features, instant feedback, and simple and attractive display, which can increase motivation and learning engagement. The results of the observation also showed that students were more active and enthusiastic in using this application compared to traditional learning methods. Thus, Duolingo can be said to be effective as an AI-based learning medium to improve vocabulary mastery of junior high school students in Indonesia.